Building Children Character Through Moral Values in The Adventure of Pinocchio - Irma Ulfia Farahani; Wahju Kusumajanti; Zulidyana Dwi Rusnalasari (Universitas Islam Negeri Sunan Gunung Djati, 2021)
This study attempts to analyze a fairy tale novel entitled “The Adventure of Pinocchio”, which talks about the story of the irrepressible marionette who longed to become a real boy. This study focuses on revealing the categories of moral value and describing the building children's character implied in this novel. To analyze this novel, the researcher uses two principles theory to find out the objectives of the studies. There are moral values argued by Linda & Eyre and the theory of children’s character building based on Lewis. The method of this study is qualitative research, which means it does not need statistical procedure to analyze the material. This study merely uses “The Adventure of Pinocchio,” a novel by Carlo Collodi, translated into English version by Carol Della Chiesa as the primary data source. At the same time, the secondary data sources are taken from other literary books and related references to support and complete the primary data. As a result, the researcher finds that some elements of moral values such as love and affection, sensitivity and not-selfish, bravery, self-discipline, and moderation occurred in the content of the novel. Meanwhile, building children's character can be implied through “The Adventure of Pinocchio's” fairy tale: honesty, responsible, regard, respect, and compassionated. Keywords: Fairy Tale, Moral Value, Building Children Character